2021
DOI: 10.3390/atmos12070905
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability, Dengue Vector Abundance and Dengue Fever Cases in Dhaka, Bangladesh: A Time-Series Study

Abstract: Numerous studies on climate change and variability have revealed that these phenomena have noticeable influence on the epidemiology of dengue fever, and such relationships are complex due to the role of the vector—the Aedes mosquitoes. By undertaking a step-by-step approach, the present study examined the effects of climatic factors on vector abundance and subsequent effects on dengue cases of Dhaka city, Bangladesh. Here, we first analyzed the time-series of Stegomyia indices for Aedes mosquitoes in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 53 publications
1
18
0
2
Order By: Relevance
“…In contrast to the above findings, a study conducted in Pakistan revealed that that the highest occurrence of dengue was reported when the rainfall is low (Fareed, Ghaffar, & Malik, 2016). This evidence is supported by the findings of a study conducted in Bangladesh, India and Sri Lanka and Pakistan (Islam, Emdad Haque, Hossain, & Hanesiak, 2021;Netrananda & Mani, 2021); (Mukhtar et al, 2021). Studies from Thailand, India and Sri Lanka have revealed that there is no significant association between dengue and rainfall (Chaiphongpachara et al, 2017;Goto et al, 2013;Noppradit et al, 2021;Pandey et al, 2012;Salam, 2018;Wijegunawardana et al, 2019).…”
Section: Impact Of Rainfall On Denguementioning
confidence: 88%
“…In contrast to the above findings, a study conducted in Pakistan revealed that that the highest occurrence of dengue was reported when the rainfall is low (Fareed, Ghaffar, & Malik, 2016). This evidence is supported by the findings of a study conducted in Bangladesh, India and Sri Lanka and Pakistan (Islam, Emdad Haque, Hossain, & Hanesiak, 2021;Netrananda & Mani, 2021); (Mukhtar et al, 2021). Studies from Thailand, India and Sri Lanka have revealed that there is no significant association between dengue and rainfall (Chaiphongpachara et al, 2017;Goto et al, 2013;Noppradit et al, 2021;Pandey et al, 2012;Salam, 2018;Wijegunawardana et al, 2019).…”
Section: Impact Of Rainfall On Denguementioning
confidence: 88%
“…Obtaining a dengue dataset that is completely fit for the model and has all characteristics is difficult to find. There are many issues faced by the researchers in this area like i) data being incomplete, ii) data being not available in required time lag like weekly or monthly and for a specific time-period and iii) data that is available only on a macro level like country-level or state-level and not on micro-level like city-level ( 15 , 28 , 45 , 54 , 63 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 shows the steps followed in information pre-processing. The major concern for reviewers is missing data and data not being available completely ( 28 ). Jorge et al ( 29 ) developed a three-stage to take the missing values in the dataset wherein first stage parameters with more than 20 per cent of missing values were eliminated.…”
Section: Analytical Review Of Predicting Dengue Outbreakmentioning
confidence: 99%
See 2 more Smart Citations